Analysis of Increasing the Income of Rice Farmers in Pulau Sarak Village Through the Use of Biosaka in 2021-2022 - Novian; Alfani Rizki; Angel Violina Sipahutar; Dias Nurisma; Endang Rohana Astriani Sitompul; Forman Sebastian Sibarani; Frederika Evelin Purnama; Nurliyani; Reindhard Juliantonius Simamora; Rifky Putra Ramadhan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the impact of Biosaka utilization on the increased income of rice farmers in Pulau Sarak Village. Biosaka is an innovative biotechnology-based product designed to enhance rice plant productivity. The research methodology involved field surveys, farmer interviews, and income data analysis. Data was collected before and after the implementation of Biosaka to compare changes in farmers' income. The findings of this research reveal that the utilization of Biosaka has yielded a positive impact on the income of rice farmers in Pulau Sarak Village. Rice plant productivity significantly increased following the use of Biosaka, ultimately leading to higher harvest yields. The larger harvest outputs have significantly contributed to the farmers' income. Income data analysis also indicates that farmers utilizing Biosaka experienced a higher increase in income compared to those not using the product. Furthermore, factors such as farmers' comprehension of Biosaka utilization, technical support provided, and environmental conditions also influence the effectiveness of Biosaka usage. This study provides critical insights for the development of innovative products in the agricultural sector and offers perspectives on how biotechnology can contribute to improving farmers' income. In conclusion, Biosaka utilization holds the potential to considerably enhance the income of rice farmers in Pulau Sarak Village. However, the successful implementation of this product also hinges on farmers' understanding, technical support, and environmental factors. The results of this research are expected to serve as a reference for agricultural development policies in similar regions and can motivate the development of similar products to support the well-being of farmers worldwide.